Analysis of the Effect of Blended Learning Method on New Students of PTP UNM - Anita Candra Dewi; Fitriani; Magfira Tunnisa; Azizah Tandiea Paembonan; Devista Gresya Kala’tasik; Zulfikar Fadil (International Journal of Sustainability in Research, 2023)
This study aims to determine the effect of blended learning method on new students of technology education UNM. This research is a quantitative study that refers to a research methodology based on the concept of positivism and is carried out by selecting certain samples and populations. The sample of this study were new students with the number of subjects in this study were 36 people. The data collection technique used in the study used a questionnaire distributed via google form which included 20 statements. Based on the results of data analysis, it can be concluded that new students feel that learning using blended learning has effectiveness and flexibility in its implementation, but has disadvantages in face-to-face and online methods respectively. The disadvantages of online learning include students not being able to adapt to the campus environment, inadequate internet networks, students cannot understand the material properly and monotonous online learning makes students pay less attention to it and even tend to find it boring with such long learning hours while offline learning is considered to be able to cover class conditions that are not in accordance with its capacity, can interact with friends and lecturers, and learning hours are more scheduled.